PENGARUH EDUKASI KEUANGAN, LITERASI KEUANGAN, FINANCIAL TECHNOLOGY TERHADAP PERILAKU DALAM MENGELOLA KEUANGAN PADA MAHASISWA AKUNTANSI DI KOTA MEDAN - Hamida, Novelia; Simbolon, Ramadona; Elviani, Sri (UNIVERSITAS DHARMAWANGSA, 2025)
This study was conducted to analyze the influence of financial education, financial literacy, and financial technology on the financial management behavior of accounting students in Medan City. Students in Medan City totaling 11,825 are the focus population in this quantitative analysis. The sampling method uses non-probability sampling with a purposive sampling approach. The sample of this study was 387 students. With a quantitative approach and multiple linear regression method, data were collected from accounting students through questionnaires. The statistical method used in this study is the Statistical Program for Social Science (SPSS). The results of the study show that partially and simultaneously, the three independent variables have a significant influence on financial management behavior. Financial education provides a basic understanding of personal financial management, financial literacy helps students make the right financial decisions, and financial technology facilitates access and management of financial transactions. These findings indicate the importance of these three aspects in shaping healthy financial behavior among students.